Unanswered Questions in Pediatric Clinical Trials: Literature Review - Leyla S. Namazova-Baranova; Nilab Sadeqi; Alexander A. Baranov (Педиатрическая фармакология)
This literature review provides information on the deficit of clinically proven data on the drugs use in pediatric practice. Issues on why children are widely administrated with drugs that are normally intended for use in adults without any prior qualitative estimation of their safety and efficacy in appropriate clinical studies involving children have been analyzed. The authors considered the issues of carrying out clinical trials with the participation of children as study subjects: ethical, regulatory, and psychological aspects of this complex task. There are decisions for every of the listed aspect. The authors of analyzed sources and the authors of this article believe that these decisions may help to address all the challenges and evade the incorrect assessment and interpretation of initial data by children’s parents and adoptive parents (legal representatives). Issues of doctors’ alertness were considered separately. Information and excerpts from regulatory acts were given, as well as information from publications on awareness raising and in support of doctors-researches. This literature review has been carried out to solve problems of information gap in the field of drugs safety and efficacy in pediatric practice. The disclosure of discussion points for clinical trials with children will ultimately help to improve the quality of healthcare provided to children in the future and take advantage of recent technologies used in patients’ cohorts of other age groups.